Control of navigation and feeding actions of a continuum arm for in-situ repair - Palmer, David (2016)
Maintenance and repair of large or complex structures is often an afterthought post-production. Conventional restoration techniques involve removing components and performing operation in a workshop. For many of these structures, it is not feasible. As such, an EU Project was setup to create a generic in-situ repair tool. This was comprised of two individual robots. This study follows the development of the control algorithms for one of the systems, devised as Snake Arm, which is a sub-set of the field of hyper-redundant manipulators. It consists of 12 sections, which means there are 25 degrees of freedom including the feed-in mechanism. The robot has been demonstrated for two main scenarios: the inspection and repair of a gas turbine engine whilst it is still attached to an aeroplane wing, and inspection of an RPV head inside a nuclear reactor while mounted on the other robot.